THE USE OF YOUTUBE VIDEOS TO IMPROVE STUDENTS’ ABILITY IN WRITING EXPLANATION TEXT - Marlina; Usman Kasim; Siti Sarah Fitriani (STKIP Siliwangi, 2024)
This study aims to investigate the improvement of students' ability in writing Explanation text using YouTube videos as teaching media in writing class. The Classroom Action research (CAR) proposed by Kemmis and Taggart was applied. This research is qualitative research with 30 students of class XI MIPA of SMAN 12 Banda Aceh as research subjects. In collecting the data, a writing test and observation checklist were used. The pre-test and post-test were given to find out the students' writing ability before and after the treatment given. The data revealed that the mean score of post test 1 and post test 2 were higher than pre test. It was gradually increased from 62,70 to 73,30 in post test 1, and 78,80 in post test 2. This indicates that there was a significant improvement in students' writing ability after implementing YouTube videos as media to teach writing explanation text. Thus, it can be concluded that the implementation of YouTube videos can improve students' ability in writing explanation text at XI MIPA 1 SMA Negeri 12 Banda Aceh. It is suggested to other researchers to conduct further research related to the use of YouTube videos not only for writing, but also for reading, speaking, and listening.